Mechanisms of tumor resistance to immune checkpoint blockade and combination strategies to overcome resistance - Zhou, Xiaoting; Ni, Yanghong; Liang, Xiao; Lin, Yi; An, Biao; He, Xiang; Zhao, Xia (Frontiers in Immunology, 2022)
Immune checkpoint blockade (ICB) has rapidly transformed the treatment paradigm for a range of cancer types. Multiple single or combinations of ICB treatments have been approved by FDA, providing more options for the treatment of patients with advanced cancer. However, due to the primary and acquired drug resistance, the majority of patients could not benefit from these immunotherapies. Thus, a better understanding of the mechanisms of ICB resistance is urgently needed to improve the clinical outcomes of patients. Here we focused on the changes in biological functions of CD8+ T cells to elucidate the underlying resistance mechanisms of ICB therapies, and summarized the advance of coping strategies. Clearly, combinational ICB approaches and individualized immunotherapies require further in-depth investigation, to facilitate longer-lasting efficacy and greater safety of ICB in a wider range of patients.